Bacterial physiology : a molecular approach - El-Sharoud, Walid M. (Springer, 2008)
The application of new molecular methodologies in the study of bacterial behaviour and cell architecture has enabled new revolutionary insights and discoveries in these areas. While this has also raised a number of scientific mysteries about bacteria, it certainly improved our understanding of these organisms as complex and adaptive entities rather than just simple tiny buckets of enzymes. The value of this recent knowledge in bacterial physiology is not only restricted to fundamental biology, but it also extends to biotechnology and drug-discovery disciplines where understanding cell behaviou.